Mesocosm Environmental Data and TA Methodology from Quantifying susceptibility of marine invertebrate biocomposites to dissolution in reduced pH - Matthew Chadwick; Elizabeth M. Harper; Anaëlle Lemasson; John I. Spicer; Lloyd S. Peck (2019)
Variations in mesocosm environmental parameters (pH, temperature, salinity, total alkalinity and pCO2) over a period of 100 days for two pH treatments. Methodology used to calculate total alkalinity